Estudio del desamargado por germinación y lavado de dos ecotipos, dos variedades de chocho (lupinus mutabilis sweet) y dos índices de madurez. - Coyago Quishpe, Mayra Elizabeth (2021)
This research study was carried out in order to evaluate the lupine debittering process (Lupinus mutabilis sweet) by the germination and washing method. Lupine is a legume with high nutritional value. However, lupine contains alkaloids that give it a bitter flavor and it can even become toxic. It prevents the lupine from being consumed directly. Therefore, it must experience a debittering process, for which the raw material was received in two varieties (INIAP 450 Andino and INIAP 451 Guaranguito) and two Ecotypes (local Native and local Peruvian), in a state of maturity; green and dry. Cleaning, classification, disinfection, scarification were carried out, followed by the four basic phases that are the hydration of the grain for 12 hours in the case of green lupine and 24 hours in the case of dry lupine, the germination phase that consists of the appearance of the insipient stalk of the grain within 5 to 12 days; cooking, in this phase the capacity of the grain continues to germinate and eliminates the alkaloids. Finally, the washing phase that consists of changing the water daily in order to eliminate the remaining alkaloids from the legume, all these phases must be under conditions of humidity, temperature and oxygenation. An experimental design of AxBxC with 24 treatments and two replications was carried out to determine the best treatment. A physicochemical and microbiological analysis was applied to the best treatment, corresponding t17 (a3b3c1) Native local ecotype, 12-day germination and the green maturity index, which presented ideal ranges according to the requirements of the debittered lupine, with a pH of (6.1), humidity (75.55%), ash (2.04%) and alkaloids (0.03%). A microbiological analysis was also carried out at the best treatment, the results are the following: molds (<10 CFU / cm3), yeasts (3.8x101 CFU / cm3), total coliforms (3.0x101 nmp / g) and Escherichia coli (absence).